The wheat Phs-A1 pre-harvest sprouting resistance locus delays the rate of seed dormancy loss and maps 0.3 cM distal to the PM19 genes in UK germplasm - Shorinola, Oluwaseyi; Bird, Nicholas; Simmonds, James; Berry, Simon; Henriksson, Tina; Jack, Peter; Werner, Peter; Scholefield, Duncan; Balcárková, Barbara; Valárik, Miroslav; Holdsworth, Michael J.; Flintham, John; et al. (Oxford University Press, 2016)
The precocious germination of cereal grains before harvest, also known as pre-harvest sprouting, is an important source of yield and quality loss in cereal production. Pre-harvest sprouting is a complex grain defect and is becoming an increasing challenge due to changing climate patterns. Resistance to sprouting is multi-genic, although a significant proportion of the sprouting variation in modern wheat cultivars is controlled by a few major quantitative trait loci, including Phs-A1 in chromosome arm 4AL. Despite its importance, little is known about the physiological basis and the gene(s) underlying this important locus. In this study, we characterized Phs-A1 and show that it confers resistance to sprouting damage by affecting the rate of dormancy loss during dry seed after-ripening. We show Phs-A1 to be effective even when seeds develop at low temperature (13 °C). Comparative analysis of syntenic Phs-A1 intervals in wheat and Brachypodium uncovered ten orthologous genes, including the Plasma Membrane 19 genes (PM19-A1 and PM19-A2) previously proposed as the main candidates for this locus. However, high-resolution fine-mapping in two bi-parental UK mapping populations delimited Phs-A1 to an interval 0.3 cM distal to the PM19 genes. This study suggests the possibility that more than one causal gene underlies this major pre-harvest sprouting locus. The information and resources reported in this study will help test this hypothesis across a wider set of germplasm and will be of importance for breeding more sprouting resilient wheat varieties.